Assessment of a Micropatterned Hepatocyte Coculture System to Generate Major Human Excretory and Circulating Drug Metabolites - Wang, Wendy WeiWei; Khetani, Salman R.; Krzyzewski, Stacy; Duignan, David B.; Obach, R. Scott (Drug metabolism and disposition, 2010)
Metabolism is one of the important determinants of the overall disposition of drugs, and the profile of metabolites can have an impact on efficacy and safety. Predicting which drug metabolites will be quantitatively predominant in humans has become increasingly important in the research and development of new drugs. In this study, a novel micropatterned hepatocyte coculture system was evaluated for its ability to generate human in vivo metabolites. Twenty-seven compounds of diverse chemical structure and subject to a range of drug biotransformation reactions were assessed for metabolite profiles in the micropatterned coculture system using pooled cryopreserved human hepatocytes. The ability of this system to generate metabolites that are >10% of dose in excreta or >10% of total drug-related material in circulation was assessed and compared to previously reported data obtained in human hepatocyte suspensions, liver S-9 fraction, and liver microsomes. The micropatterned coculture system was incubated for up to 7 days without a change in medium, which offered an ability to generate metabolites for slowly metabolized compounds. The micropatterned coculture system generated 82% of the excretory metabolites that exceed 10% of dose and 75% of the circulating metabolites that exceed 10% of total circulating drug-related material, exceeds the performance of hepatocyte suspension incubations and other in vitro systems. Phase 1 and phase 2 metabolites were generated, as well as metabolites that arise via two or more sequential reactions. These results suggest that this in vitro system offers the highest performance among in vitro metabolism systems to predict major human in vivo metabolites.